Application of The Kirkpatrick Level 3 Model to Evaluate The Human Resource Training Program at PT X - Alalusy, Allamah; Rahayuningsih, Idha (Tarqabin Nusantara Group, 2024)
Learning is a process that takes place to gain knowledge and knowledge. Learning activities carried out in the corporate or work world are better known as training and development activities. With training activities, it is hoped that there will be an increase in employee knowledge, skills and attitudes, so that company goals can be achieved. Training evaluation is a stage that should be an integral part of the training program. PT X is one of the companies that has also managed Learning & Capability Development, the implementation of which continues to be in the process of development and improvement. The process of Training Needs Analysis, implementation and evaluation has been carried out and carried out in 3 stages, however the evaluation of stage 3 cannot yet be carried out because there is still the problem of not having tools implemented in the Company to carry out level 3 evaluations. The evaluation model used is known as Donald L. Kirkpatrick.